2003
DOI: 10.1021/cm021013+
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Gold Nanoparticles on Silica Spheres:  A Sonochemical Approach

Abstract: Gold nanoparticles with an average size of ∼5 nm were deposited on the surface of preformed silica submicrospheres with the aid of power ultrasound. The sonochemical reduction was carried out by ultrasonic irradiation in an argon atmosphere at room temperature. Ultrasonic irradiation of a slurry of silica submicrospheres, chloroauric acid (HAuCl4), and ammonia in an aqueous medium for 45 min yielded a gold−silica nanocomposite. By controlling reaction conditions, we could achieve the deposition of metallic gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(121 citation statements)
references
References 44 publications
2
111
0
8
Order By: Relevance
“…It is highly likely that copper nanocrystallites act as nucleation sites accelerating silica's transition from the amorphous to crystalline phase during the calcination process. This is in agreement with previous studies in which the addition of a small amount of metal ions affected silica's crystallization kinetics [32,33]. Moreover, in the 7.7 wt % copper loaded silica material, trace peaks possibly corresponding to tenorite (JCPDS # 3-884) and copper phosphate (JCPDS # 44-182) phases could also be detected.…”
Section: Synthesis In Phosphate Buffer (Pb)supporting
confidence: 92%
“…It is highly likely that copper nanocrystallites act as nucleation sites accelerating silica's transition from the amorphous to crystalline phase during the calcination process. This is in agreement with previous studies in which the addition of a small amount of metal ions affected silica's crystallization kinetics [32,33]. Moreover, in the 7.7 wt % copper loaded silica material, trace peaks possibly corresponding to tenorite (JCPDS # 3-884) and copper phosphate (JCPDS # 44-182) phases could also be detected.…”
Section: Synthesis In Phosphate Buffer (Pb)supporting
confidence: 92%
“…All reagents were > 99 % purity and were used as received. 2 or Al 2 O 3 powder was stirred with 10 ml of 1X10 -2 M oleic acid in methanol at 500 rpm on a magnetic stirrer at room temperature until evaporation. 10 ml of 1X10 -2 M aqueous AgNO 3 solution, sufficient to yield a final loading of silver nanoparticles of 1 wt% (calculated with respect to the initial mass of oxide), was added to the dried sample.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous reports describe the synthesis of such composite materials, with particular emphasis on immobilization of noble metal nanoparticles on oxides such as SiO 2 [1][2][3], TiO 2 [4][5][6][7][8][9][10] and Al 2 O 3 [11][12][13][14][15][16]. These oxides are of interest due to their ready availability, ease of handling, low toxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated their potential applications in LC as mentioned above. Recently, synthesis of nanometer-sized core-shell structures consisting of silica core and precious metal shell (e. g., Au, Pt, Ag) as well as precious metal core and silica shell has become an increasingly important topic [53][54][55][56][57][58][59][60][61]. The precious metal nanoparticles are of several nanometers in diameter in the resulting core-shell composites of several hundred nanometers in size.…”
Section: Future Possibilities For Nanomaterialbased Stationary Phasesmentioning
confidence: 99%